Determinants for the diffusion of renewable energy technologies – framework for assessing major factors in investors' decision-making processes. (23rd February 2015) - Boie, Inga; Ragwitz, Mario; Held, Anne
Broad deployment of renewable energy (RE) technologies is a primary objective of the European climate strategy. All European member states developed policy strategies and financial support mechanisms for renewable electricity. However, apart from the remuneration scheme, non-economic and regulatory factors influence market diffusion of RE-technologies. Diffusion results from decisions of individual actors and their perceptions of market attractiveness. Therefore, understanding the basic determinants governing their decisions is crucial to anticipate diffusion processes under given framework conditions and to develop policy tools pinpointing the essential factors and enabling RE-deployment cost- and time-efficiently. We propose a robust set of determinants for RE-diffusion and suggest respective data sources allowing for objective assessment of framework conditions on country level. Results are based on literature research, interviews and expert workshops. They are utilisable as input for construction of benchmarking tools (composite indicators) and energy economic modelling (diffusion models) and provide a sound basis for evaluation of RE-regulations and efficient policy design.